Obesity‐induced lymphatic dysfunction is reversible with weight loss. (9th October 2016) - Nitti, Matthew D.; Hespe, Geoffrey E.; Kataru, Raghu P.; García Nores, Gabriela D.; Savetsky, Ira L.; Torrisi, Jeremy S.; Gardenier, Jason C.; Dannenberg, Andrew J.; Mehrara, Babak J.
Abstract : Key points: Obesity induces lymphatic leakiness, decreases initial lymphatic vessel density, impairs collecting vessel pumping and decreases transport of macromolecules. Obesity results in perilymphatic inducible nitric oxide synthase (iNOS) expression and accumulation of T cells and macrophages. Deleterious effects of obesity on the lymphatic system correlate with weight gain. Weight loss restores lymphatic function in obese animals and decreases perilymphatic iNOS and inflammatory cell accumulation. Abstract: Although clinical and experimental studies have shown that obesity results in lymphatic dysfunction, it remains unknown whether these changes are permanent or reversible with weight loss. In the current study, we used a mouse model of diet‐induced obesity to identify putative cellular mechanisms of obesity‐induced lymphatic dysfunction, determine whether there is a correlation between these deleterious effects and increasing weight gain, and finally examine whether lymphatic dysfunction is reversible with diet‐induced weight loss. We report that obesity is negatively correlated with cutaneous lymphatic collecting vessel pumping rate ( r = –0.9812, P < 0.0005) and initial lymphatic vessel density ( r = –0.9449, P < 0.005). In addition, we show a significant positive correlation between weight gain and accumulation of perilymphatic inflammatory cells ( r = 0.9872, P < 0.0005) and expression of inducible nitric oxide synthase (iNOS; r = 0.9986, P < 0.0001). Weight loss resulting from conversion to a normal chow diet for 8 weeks resulted in more than a 25% decrease in body weight and normalized cutaneous lymphatic collecting vessel pumping rate, lymphatic vessel density, lymphatic leakiness, and lymphatic macromolecule clearance (all P < 0.05). In addition, weight loss markedly decreased perilymphatic inflammation and iNOS expression. Taken together, our findings show that obesity is linearly correlated with lymphatic dysfunction, perilymphatic inflammation and iNOS expression, and that weight loss via dietary modification effectively reverses these deleterious effects. Key points: Obesity induces lymphatic leakiness, decreases initial lymphatic vessel density, impairs collecting vessel pumping and decreases transport of macromolecules. Obesity results in perilymphatic inducible nitric oxide synthase (iNOS) expression and accumulation of T cells and macrophages. Deleterious effects of obesity on the lymphatic system correlate with weight gain. Weight loss restores lymphatic function in obese animals and decreases perilymphatic iNOS and inflammatory cell accumulation.